Profesionalisme Guru Dalam Menjalankan Tugas Mengajar Dan Mendidik Siswa Di Sekolah - Ndolu, Faransina (JURNAL LUXNOS, 2025)
Teacher professionalism is a main and strategic component in the national education system. Teachers have the dual role of transferring knowledge (teaching) and instilling moral, social, and spiritual values (educating) in students. Law No. 14 of 2005 affirms that teachers are professionals crucial for achieving national education goals. Ideally, teachers should possess four core competencies: pedagogical, personal, professional, and social, and be able to effectively plan, implement, and evaluate learning. However, teacher professionalism in Indonesia faces significant challenges. Studies reveal consistently low performance, the use of conventional lecture methods, limited use of technology, and hindrances from external factors like insufficient training and high administrative burdens. Teacher certification has not fully resulted in significant improvements in teaching quality, and internal factors like low motivation also play a role. This situation highlights a gap between the ideal conditions and reality, necessitating in-depth research. This study aims to bridge this gap by viewing teacher professionalism holistically, emphasizing the balance between teaching and educating tasks (character building). The novelty of this research lies in the exploration of factors like values, motivation, and professional ethics, while considering the context of the school environment. Employing a descriptive quantitative approach, the research will outline the level of teacher professionalism, covering aspects such as competence, the impact of certification, school principal leadership, organizational culture, and digital literacy. The findings are expected to serve as a factual basis for formulating more effective and sustainable strategies for enhancing teacher professionalism in Indonesian education.